Study of Physics Concepts in Cave Exploration Activities to Develop Physics Edupark Digital Book for Senior High School Students - Pratiwi Ineke Anwar; Hamdi Rifai; Ferdinal Ferdinal; Siti Zulaikah; Husna Husna; Tessa Destia Putri Lisa; Dini Fitriani (Postgraduate, University of Mataram, 2023)
Even though the concept of physics is very important in daily activities, the cave exploration activities (caver and or cave tourists) are not based on of physics concepts. In addition, the teachers do not realize that through caves and it exploration activities can be used to learn the physics concepts. This research aims to study the physics concepts in caving activities where it used to develop of physics edupark digital books for senior high school students. This is preliminary research that part of research and development method by using the Plomp model where the study consists of teacher, student, and material potential analysis. This study has been resulting that many concepts while cave exploration activities. It can be used to lean the physics concepts then developing an Edupark physics digital enrichment book as a demand of the Merdeka’s Curriculum. The learning activities growth from the abilities of students who emphasize contextual learning where the students building meaningful understanding through learning and optimizing technology in learning